﻿Species of Peperomia (Piperaceae) from the Saña River Valley, Peru - Guillermo Eloy Pino Infante; Marie-Stéphanie Samain; Joaquina Adelaida Albán Castillo; Luis Enrique Aarón Alomía Collazos (PhytoKeys, 2023)
The Saña River Valley in Northern Peru is unusual for the western slopes of the Peruvian Andes because of its nearly year-round regime of precipitation instead of marked seasonal dry winters. This results in unexpected plant diversity. We surveyed the species of Peperomia (Piperaceae), occurring in this valley from 300 to 3000 m elevation, based on the study of specimens from ten herbaria and field collections, resulting in a total of 81 accessions, of which 48 were made by the authors. We found 16 different taxa: Peperomia cacaophila, from Ecuador, is reported for the first time in Peru; P. cymbifolia, P. dolabriformis and P. emarginulata are reported for the first time for the Saña River Valley; other widely distributed species like P. fraseri, P. galioides, P. haematolepis, P. hispidula, P. inaequalifolia, P. microphylla, and P. rotundata were also found. Five species new to science are described: P. pilocarpa, P. riosaniensis, close to P. palmiformis from Amazonas; P. sagasteguii, related to P. trinervis, P. symmankii, close to P. ricardofernandezii from Piura, and P. vivipara, related to P. alata. A key to the species of Peperomia from the Saña River Valley, based on vegetative characters, is provided.